2021
DOI: 10.3390/antiox10020262
|View full text |Cite
|
Sign up to set email alerts
|

Rebaudioside A Enhances Resistance to Oxidative Stress and Extends Lifespan and Healthspan in Caenorhabditis elegans

Abstract: Non-nutritive sweeteners are widely used in food and medicines to reduce energy content without compromising flavor. Herein, we report that Rebaudioside A (Reb A), a natural, non-nutritive sweetener, can extend both the lifespan and healthspan of C. elegans. The beneficial effects of Reb A were principally mediated via reducing the level of cellular reactive oxygen species (ROS) in response to oxidative stress and attenuating neutral lipid accumulation with aging. Transcriptomics analysis presented maximum dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…elegans. SOD -3 controlled oxidative stress via reducing ROS and enhanced the lifespan . Chrysin treatment at 20, 40, 80, and 100 μM concentrations exhibited a significant increase in SOD -3 expression as compared to untreated groups (Figure A).…”
Section: Resultsmentioning
confidence: 95%
“…elegans. SOD -3 controlled oxidative stress via reducing ROS and enhanced the lifespan . Chrysin treatment at 20, 40, 80, and 100 μM concentrations exhibited a significant increase in SOD -3 expression as compared to untreated groups (Figure A).…”
Section: Resultsmentioning
confidence: 95%
“…In recent years, transcriptomics has been widely used to reveal differences in the expression of genes in biological functions and to discover the mechanisms or targets of drugs. By using transcriptomics analysis, Li et al found that Rebaudioside A could protect Caenorhabditis elegans from oxidative stress via regulating TOR and PI3K/Akt pathways [ 51 ]. RNA sequencing results of this study indicated that the MAPK and NF-κB pathways may be involved in the potential anti-inflammatory mechanism of EOZS.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronized worms were grown until the L4 stage. They were washed with M9 buffer and collected by centrifugation [ 25 ]. To prepare QBLP-supplemented food, appropriate amounts of QBLP (0.02, 0.2, and 2 g/mL) were dissolved in the NGM.…”
Section: Methodsmentioning
confidence: 99%